Metabolic adaptation of the clam Ruditapes philippinarum during air exposure and the positive effects of sodium nitroprusside pretreatment - Zheng, Zhilong; Huo, Zhongming; Huang, Kaiyue; Jiang, Min; Yan, Xiwu; Liu, Yang; Qin, Yanjie (Frontiers in Physiology, 2023)
The Manila clam (Ruditapes philippinarum), as one of the shellfish living in the intertidal zone, is known for its strong ability to withstand air exposure. Sodium nitroprusside (SNP), a donor of nitric oxide (NO), has been shown to be useful for antioxidant and immune regulation in aquatic animals. In this study, an untargeted metabolomics (LC–MS/MS) technique was employed for the first time in Manila clam to analyze the metabolic and histological impacts after air exposure and the positive effects of SNP pretreatment. During air exposure, a significant increase in taurine, L-glutamate, and several polyunsaturated fatty acids in clams was detected, which indicates that clams may experience inflammatory reactions, oxidative stress, and an increase in blood ammonia content. When clams were exposed to SNP for 6 h, arginine, spermine, L-glutamic acid, and glutathione content were all upregulated, indicating that the SNP exposure induced NO production and improved antioxidant capacity in clams. When the clams were exposed to air after SNP pretreatment, there were no significant differences in the levels of taurine, L-glutamate, or aliphatic acids between the experimental and control groups. Gill tissue was more severely damaged in clams directly exposed to air than in those that experienced air exposure after SNP pretreatment, especially in clams exposed to air for a long time (72 h). Both metabolomics and tissue section structure indicated that SNP pretreatment decreased the stress responses caused by air exposure in R. philippinarum. These findings provided fresh insights and a theoretical foundation for understanding the tolerance to air exposure and physiological functions of SNP (or NO) in R. philippinarum.